Gestão socioambiental no Centro de Energias Alternativas e Renováveis da UFPB: análise sob a ótica da agenda ambiental na administração pública (A3P) - Pereira, Valdeniza Delmondes (2025)
Discussions on sustainability in recent decades have led to significant changes in concepts related to socio-environmental management within institutions. In Brazil, the government has encouraged public institutions to adopt tools that support socio-environmental management. To this end, the Ministry of the Environment established the Environmental Agenda in Public Administration (A3P), a socio-environmental management program designed to enhance efficiency in public activities and promote environmental preservation across all public agencies. This study aims to analyze the operational activities of the Alternative and Renewable Energy Center (CEAR) at UFPB based on the thematic axes of the A3P. The research adopts a documentary and bibliographic approach and follows an exploratory-descriptive methodology with a quantitative-qualitative perspective. The study seeks to understand CEAR employees' perceptions regarding socio-environmental issues related to the Center. Descriptive statistical analysis was applied, emphasizing trends identified as the most frequent responses within each question group. The results indicate significant challenges in certain areas of socio-environmental management at the Center. However, progress has been made in utilizing alternative renewable energy sources, and structural accessibility issues have been addressed with the construction of a new administrative headquarters, fostering greater inclusion within the academic community.